Pengaruh Penerapan Model Pembelajaran Project Based Learning Terhadap Keaktifan Siswa Kelas VIII Mata Pelajaran IPS di SMPN 1 Ngantru Tulungagung - Alisa Ristianing Putri; Jani Jani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is motivated because the learning model used is still conventional. Students also lack interest in social studies learning and only rely on LKS books in learning, resulting in students being less active in learning. This study aims to find out the project based learning model has a significant effect on student activity and how much influence the application of the project based learning model has on student activity. This research is a quantitative research with a quasy experimental type. The instruments used are questionnaires, observation, and documentation. The population used is all class VIII. The sample for class VIII-C is the student experimental class and class VIII-D is the control class with 38 students each. The results of this study indicate that: (1) there is a significant influence between the project based learning learning model on student activity with a value of tcount = 16.13 and ttable of 1.991 at a significance level of 5%, namely so that the value of tcount>ttable with an average value of the experimental class is 89 .5 while the control class is 69.5, (2) the magnitude of the influence of the project-based learning model on student activity in obtaining a presentation value of 82% is included in the high category.